$\newenvironment {prompt}{}{} \newcommand {\ungraded }[0]{} \newcommand {\HyperFirstAtBeginDocument }[0]{\AtBeginDocument }$
1 : Compute the following numeric exponential value.
• $\sage {p1b1}^{\sage {p1pwr1}} = \answer {\sage {p1ans1}}$
• $\left (\frac {1}{\sage {p1b1}}\right )^{\sage {p1pwr1}} = \answer {\sage {p1ans2}}$
• $\left (\sage {p1b1}\right )^{-\sage {p1pwr1}} = \answer {\sage {p1ans2}}$
• $\left (\frac {1}{\sage {p1b1}}\right )^{-\sage {p1pwr1}} = \answer {\sage {p1ans1}}$
2 : Compute the following numeric exponential value.
• $\sage {p2b1}^{\sage {p2pwr1}} = \answer {\sage {p2ans1}}$
• $\left (\frac {1}{\sage {p2b1}}\right )^{\sage {p2pwr1}} = \answer {\sage {p2ans2}}$
• $\left (\sage {p2b1}\right )^{-\sage {p2pwr1}} = \answer {\sage {p2ans2}}$
• $\left (\frac {1}{\sage {p2b1}}\right )^{-\sage {p2pwr1}} = \answer {\sage {p2ans1}}$
3 : Compute the following numeric exponential value.
• $\sage {p3b1}^{\sage {p3pwr1}} = \answer {\sage {p3ans1}}$
• $\left (\frac {1}{\sage {p3b1}}\right )^{\sage {p3pwr1}} = \answer {\sage {p3ans2}}$
• $\left (\sage {p3b1}\right )^{-\sage {p3pwr1}} = \answer {\sage {p3ans2}}$
• $\left (\frac {1}{\sage {p3b1}}\right )^{-\sage {p3pwr1}} = \answer {\sage {p3ans1}}$
4 : Compute the following numeric exponential value.
• $\sage {p4b1}^{\sage {p4pwr1}} = \answer {\sage {p4ans1}}$
• $\left (\frac {1}{\sage {p4b1}}\right )^{\sage {p4pwr1}} = \answer {\sage {p4ans2}}$
• $\left (\sage {p4b1}\right )^{-\sage {p4pwr1}} = \answer {\sage {p4ans2}}$
• $\left (\frac {1}{\sage {p4b1}}\right )^{-\sage {p4pwr1}} = \answer {\sage {p4ans1}}$